Modulation Imaging Contrast Agent for Cancer - Fawwaz, Muammar (Universitas Muslim Indonesia, 2024)
Molecular imaging, also known as molecular imaging, is a medical technique used to visualize and analyze biological molecules in the human or animal body. According to the Society of Nuclear Medicine and Molecular Imaging's website,